The perceptions and preferences of generation z regarding music festivals in Portugal - investigating generation z´s attitudes towards music festivals In Portugal - Batalha, Pedro José Oliveira (2023)
With the recent growth of the music festival industry in Portugal and Generation Z being able to spend more on experiences than ever before, it has become relevant to understand their perceptions and preferences regarding the subject. This thesis addresses this challenge by employing preliminary interviews with experts and consumers, perceptual mapping, and conjoint analysis. It has been concluded that the main drivers in festival ticket purchasing among Generation Z are Line Up, Price and Sustainability, which contrasts with the experts’ common assumption that Price isn’t an important factor, thus highlighting a tension point of critical importance.